Wood characterization of Eucalyptus paniculata Smith species - Nogueira, Marta Cristina de Jesus Albuquerque; Vasconcelos, Juliano Souza; Araujo, Victor Almeida de; Christoforo, André Luis; Lahr, Francisco Antonio Rocco (Revista Principia, 2022)
Eucalypts have not been well accepted for construction use by civil societies in different nations. For the elimination of these cultural barriers, there is the demand for better knowledge of the physical-mechanical properties of these silvicultural species. Thus, the research carried out a wide characterization of the Eucalyptus paniculata Smith wood species. Based on the Brazilian standard document ABNT NBR 7190, 14 mechanical properties and 2 physical properties were evaluated. Two moisture contents were adopted to compare the wood samples in different conditions: above the fiber saturation point and dried point. Results of properties were treated statistically with a t-test. In total, 1384 repeats were reached. Only two mechanical properties did not show changes in their resistance values to moisture reduction: tangential cleavage and modulus of rupture in the perpendicular tensile to grain. Further properties showed differences in the resistances from t-test for the studied moisture reduction.